Hemorrhagic transformation in acute ischemic stroke: hemorrhagic subtypes and symptomatic intracranial hemorrhage - Luff, Marie K.; Khezri, Nicole; Miralbes, Salvador; Naravetla, Bharath; Spiotta, Alejandro M.; Loehr, Christian; Martínez-Galdámez, Mario; McTaggart, Ryan A.; Defreyne, Luc; Vega, Pedro; Zaidat, Osama O.; Price, Lori Lyn; et al. (Journal of neuroInterventional surgery, 2024)
Background Few clinical studies perform detailed analyses of subtypes of intracranial hemorrhage (ICH) after mechanical thrombectomy (MT) used to treat acute ischemic stroke. Symptomatic intracranial hemorrhage (sICH) is a formidable complication of MT and is widely used in clinical trials as a safety outcome. However, variable definitions of sICH are used across clinical studies. - Objective To radiographically subcategorize post-MT ICH development within this large cohort and examine overlap with sICH. Second, to examine the agreement of this definition of sICH with local site-reported occurrences of sICH to see how sICH rates change with modifications of the definitions used. - Methods A large cohort of patients treated with MT for acute ischemic stroke (n=1395) was analyzed to (1) radiographically characterizoe hemorrhagic subtypes of intracranial hemorrhage (ICH) occurring after MT; (2) examine associations of hemorrhagic subtypes with sICH; and (3) compare core laboratory-adjudicated occurrences of sICH with site-reported sICH. - Results The overall rate of ICH was 552/1395 patients (39.6%), and the overall rate of sICH was 47/1395 (3.4%). The most common type of ICH was hemorrhagic infarction type 1 (HI1), which represented 45.3% of all ICH cases- followed by HI2 (31.5%) and subarachnoid hemorrhage (SAH, 29.2%). Parenchymal hematoma 2 (PH2) represented only 3.3% of all ICH cases. Of the PH2 hemorrhages, only 33.3% were determined to be symptomatic. Of sICH cases, the most common ICH subtypes were HI2 (48.9%) and SAH (38.3%). Comparison of sICH rates as determined by core laboratory adjudication versus local site-reported results showed that only 14 patients were identified as having sICH with both definitions, with 47 patients total with sICH according to one definition, but not the other. - Conclusions Results of this analysis demonstrate the radiographic subtypes of ICH and also highlight the limitations of variable criteria used to define sICH, suggesting that it might be appropriate to revisit how sICH is defined post-MT. - Trial registration number Clinical trial NCT03845491.